Molecular self-assembly in indole-based benzamide derivative: Crystal structure, Hirshfeld surfaces and antimicrobial activity - Gumus, Ilkay; Solmaz, Ummuhan; Gonca, Serpil; Arslan, Hakan (European Journal of Chemistry, 2017)
Two new compounds, 1H-indole-7-amine (1) and N-(1H-indol-7-yl)-2-methylbenzamide (2) were synthesized and structurally characterized by NMR and FT-IR spectroscopic techniques. The molecular structure of compound 2 was further elucidated by single-crystal X-ray diffraction technique. Moreover, the crystal packing of compound 2 is analyzed in terms of non-covalent N-H···O, C-H···π, and parallel displaced π···π interactions. Hirshfeld surface analysis and decomposed fingerprint plots of the compound 2 were performed to visualize the presence of strong hydrogen bond N-H···O and C-H···π stacking interactions. Hirshfeld surface analysis and decomposed fingerprint plots show that the structure of compound 2 is stabilized by H···H, N-H···O, C-H···π and π···π intermolecular interactions and these interactions contribute mostly to molecular self-assembly in the crystal. In addition, compound 2 was evaluated for both their in-vitro antibacterial and antifungal activity. The obtained results have been reported, explained and compared with fluconazole and ampicillin used as reference drugs.